A comparison of Synovex-S® and STEER-oid® implants for finishing cattle - Goldy, G.; Riley, Jack G.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
There were no significant differences in performance or carcass traits for finishing cattle implanted with either Synovex-S® or STEER-oid®. The 122-day trial used 180 steers, with each treatment having 15 replicates.
Keywords: Beef; Synovex-S®; STEER-oid®; Implants; Finishing cattle